"No decisions about us without us"? Individual healthcare rationing in a fiscal ice age. (13th June 2011) - Russell, Jill; Greenhalgh, Trisha; Burnett, Andrew; Montgomery, Jonathan
Abstract : Jill Russell and colleagues examine whether patients and the public should be involved in rationing decisions about individual patient access to healthcare interventions